MENYELAMI KREATIVITAS BELAJAR: STRATEGI BERDIFERENSIASI DI KELAS RENDAH DAN TINGGI - Ernawati, Asih; Praptanti, Isnaeni; Pujiyatno, Ambar; Al-Kasyiri, Rival Fawwaz Fuadi; Dwiantoro, Farhan Naufal; Mukaromah, Umi Roisatul (Jurnal Pengabdian Masyarakat Sabangka, 2025)
This training was designed for public and private elementary school teachers in East Purwokerto who are members of the "SIPAT JUTAS" study group. The objectives were as follows: understanding the syntax of differentiated learning approaches, learning from a range of case studies in lower and upper grades, and being able to apply differentiated learning in a number of disciplines. The program began with a review of previously covered material, followed by brainstorming to introduce new topics. Participants were organized into groups and directed by speakers through case studies. A representative from each group presented the results of their discussions. The presenters then guided them through the case studies. The workshop closed with guided and group conversations about how to implement varied learning in a range of lower and upper-grade school contexts. At the end of session, participants appear to have acquired the approaches for implementing differentiated in their classrooms.